Økonomisk science fiction og kritisk anti-utopi: Dave Eggers’ The Circle, kognitiv kapitalisme og økonomisk subjektivitet - Pedersen, Martin Karlsson (Passage - Tidsskrift for litteratur og kritik, 2019)
The article gives a short introduction to the new field of “economic science fictions” and discusses an economic approach to science fiction focusing on the class aspect of utopian and anti-utopian science fiction. By tracing a common interest in the new regimes of accumulation and exploitation of cognitive labor between Cognitive Capitalism and Dave Eggers’ anti-utopian novel The Circle, the article highlights the dangerous dynamic between class-specific utopian desire and new forms of technologically driven economic exploitation.